2015
DOI: 10.5005/jp-journals-10002-1155
|View full text |Cite
|
Sign up to set email alerts
|

Location of Parathyroid Adenomas in Primary Hyperparathyroidism: Where to look?

Abstract: Purpose: Preoperative localization studies for parathyroid adenomas are very essential to perform minimal invasive parathyroidectomy (MIP) with decreased operative time and potential complications. Although most of these studies based on radiological imaging, intraoperative assessment provides the most accurate anatomical description of the location of parathyroid adenomas. In this study, we aim to evaluate the surgical variations of locations of parathyroid adenomas in patients performed parathyroid surgery f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 23 publications
(21 reference statements)
1
4
0
Order By: Relevance
“…12 None of these papers analyzed locations of adenomas specifically in patients with negative preoperative imaging. We observed a non-significant finding of right inferior to be the most common location of a single adenoma in patients with both localizing and nonlocalizing imaging, corresponding with previous study by Yazici et al 9 Our data reflecting higher rates of disease involving more than one gland (double adenomas, MGD) in patients with nonlocalizing scans correlates with previous research. 15,16 This evidence suggests that neck exploration for parathyroidectomy in patients with PHPT and negative preoperative imaging should be organized.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…12 None of these papers analyzed locations of adenomas specifically in patients with negative preoperative imaging. We observed a non-significant finding of right inferior to be the most common location of a single adenoma in patients with both localizing and nonlocalizing imaging, corresponding with previous study by Yazici et al 9 Our data reflecting higher rates of disease involving more than one gland (double adenomas, MGD) in patients with nonlocalizing scans correlates with previous research. 15,16 This evidence suggests that neck exploration for parathyroidectomy in patients with PHPT and negative preoperative imaging should be organized.…”
Section: Discussionsupporting
confidence: 91%
“…Yazici et al have described the most common surgical locations for adenomas in 243 patients with PHPT, with a predilection near the inferior lobe of the thyroid (70%), especially the right inferior location (38%). 9 Marzouki et al found the most prevalent location for adenoma in their study of 147 patients was the left inferior parathyroid gland (41%), and that pathologic glands were more likely to be inferior (74%). 10 A classification system known as the Perrier nomenclature has been developed to describe parathyroid adenoma location that has seven categories (Type A-G), however, it does not indicate laterality.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations